Pengaruh Penambahan Uap Etanol melalui Filter Udara terhadap Kinerja Mesin Diesel Menggunakan Bahan Bakar Premixed - Dani, Dani Hari Tunggal Prasetiyo; Imam Sholahuddin; Haidzar Nurdiansyah; Hari Arbiantara Basuki; Dedi Dwilaksana; Linda Kurnia Supratiningsih (Universitas Nusa Putra, 2025)
The increasing need for energy and dwindling natural reserves encourage the search for alternative energy sources. One alternative energy source is biodiesel. Biodiesel can be produced from used cooking oil through the esterification and transesterification processes. However, biodiesel sourced from plant materials has disadvantages, one of which is its low calorific value. Most studies discuss the addition of chemical additives to increase the calorific value of biodiesel. However, the addition of ethanol vapor as an air additive to increase the calorific value of biodiesel is rarely discussed. This study was conducted experimentally, the study examined the effect of adding ethanol vapor to a diesel engine through an air filter. The diesel fuel used was dexlite type diesel fuel added with biodiesel from used cooking oil as much as 10% to 30%. Testing used additional ethanol vapor channeled through an air filter with a heating temperature of 90oC to 100oC. The results of the study were in the form of crankshaft rotation, effective power, and fuel consumption. The results showed that fuel with the addition of ethanol vapor produced the highest crankshaft rotation, effective power, and fuel consumption when compared to without the addition of ethanol vapor in all variations of the given fuel composition. The highest value of crankshaft rotation, effective power is in the B0 composition with values ​​of 32.53 rev/s and 2.74 kW, respectively. While the lowest fuel consumption is in the B70 composition with the addition of ethanol vapor of 105.7 seconds.